Pooled prevalence of Escherichia coli phenotypic and genotypic antimicrobial resistance profiles in poultry: systematic review and meta-analysis - Sousa, Débora Luíse Canuto de; Limeira, Clécio Henrique; Casella, Tiago [UNESP]; Araújo, Hosaneide Gomes de; Aquino, Vitória Viviane Ferreira de; Neto, Domingos Andrade; Sobrinho, José Diniz de Souto; Azevedo, Sérgio Santos de; Santos, Carolina de Sousa Américo Batista (Springer Nature, 2025)
Escherichia coli is a zoonotic bacterium, and its resistance to antimicrobials has become an increasing problem in global health. This study aimed to determine the phenotypic and genotypic pooled prevalence of E. coli with antimicrobial resistance profiles in poultry through systematic review and meta-analysis. Articles available in scientific databases from years 2017 to 2024 were evaluated. Overall, 18 studies were included in the meta-analysis and prevalence of E. coli resistance in poultry. Estimated by the random effects model, the pooled prevalence of resistance to at least one antibiotic in E. coli isolated from poultry samples was 76.96% (95% CI = 48.74–92.15%), and multidrug-resistant isolates of 89.44% (95% CI = 75.51–95.88%). The highest prevalence was to nalidixic acid (86.67%; 95% CI = 59.32–96.67%), followed by isolates resistant to tetracycline (79.33%; 95% CI = 62.86–89.69%). Tetracycline resistance genes had the highest prevalence, with 29.78% of isolates (498/1076) positive for at least one of the three genes (tetA, tetB and/or tetC). The levels of phenotypic and genotypic prevalence of E. coli in poultry can provide a scientific basis for the control of antibiotic-resistant strains and contribute to the competent authorities to guide the management interventions that best suit the different geographical regions.
Keywords: Antibiotics; Bacterial resistance; Chickens; Genes; Hens